Candida parapsilosis Candidemia Resistance Patterns and Treatment Outcomes: An Opportunity for Antifungal Stewardship. (4th October 2017) - Fong, Gary; Ngo, Kim; Russo, Hannah; Beyda, Nicholas
Abstract: Background: Candida parapsilosis has emerged as an important fungal pathogen with mortality rates up to 30%. Recent studies show no difference in treatment outcomes for patients treated both empirically and definitively with either echinocandins or fluconazole. However, the impact of antifungal susceptibility testing and opportunities for antifungal stewardship are less clear in this patient population. The purpose of this study was to assess antifungal susceptibility rates, treatment patterns, and outcomes among patients with C. parapsilosis candidemia. Methods: This was a single-center, retrospective cohort review of adult patients with a positive blood culture for C. parapsilosis hospitalized at Baylor St. Luke's Medical Center, between 2006 and 2016. Patients with mixed or breakthrough candidemia were excluded as well as patients who expired within 3 days of candidemia onset. Results: Eighty patients with C. parapsilosis candidemia were identified of which 48 met inclusion criteria. Nine patients had infections caused by fluconazole non-susceptible isolates (19%). The most common empiric treatment choice was an echinocandin (33/48, 69%), followed by fluconazole (9/48, 19%), and combination therapy (6/48, 13%). Of the 39 patients with fluconazole susceptible isolates, only 17 were treated with fluconazole definitively (44%). Among patients who received empiric echinocandin vs. fluconazole therapy, there was no difference in 14-day mortality (9% vs. 11%, P = 1.00) or in-hospital mortality (12% vs. 11%, P = 1.00). Empiric combination therapy was the only independent risk factor for treatment failure (OR, 13.8; 95% CI, 1.4–138.3; P = 0.03). Conclusion: Treatment outcomes for patients receiving echinocandins were similar for those receiving fluconazole. At our institution, the increased incidence of fluconazole non-susceptible isolates warrants the use of echinocandins empirically. Patients were more likely to remain on echinocandin therapy even when fluconazole susceptible isolates were identified. This study reinforces the guideline suggestion that neither echinocandins nor fluconazole treatment leads to superior outcomes, but also identifies a cohort of patients in need of antifungal stewardship. Disclosures: N. Beyda, Astellas: Grant Investigator and Scientific Advisor, Research grant